Redescriptions of three species of freshwater crabs from Angola, southern Africa (Brachyura: Potamoidea: Potamonautidae) - Cumberlidge, Neil; Ahles, Katelyn M.; Daniels, Savel R. (Zootaxa, 2021)
The taxonomy of three species of freshwater crabs from Angola, Potamonautes adeleae Bott, 1968, P. macrobrachii Bott, 1953, and P. kensleyi Cumberlidge & Tavares, 2006, is revised based on examination of the paratypes and new material. Updated diagnoses, illustrations, and distribution maps are provided for these three species, and their conservation status is discussed.